PENERAPAN TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) DENGAN MULTIMEDIA DALAM PENINGKATAN PEMBELAJARAN IPA TENTANG DAUR AIR KELAS V SD - Kusuma, Hanung Purwari; Kusuma, Hanung Purwari (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Application Of Team Assisted Individualization (TAI) Type By Multimedia In Improving Natural Science Learning About Hydrology Cycle At The Fifth Grade Student Elementry School. The purpose of this study to describe and improve natural science learning about hydrology cycle fifth grade students in the elementary school, and find barriers and solutions in the application of Team Assisted Individualization (TAI) type by multimedia. This study is a collaborative classroom action research which was conducted in two cycles with 5 meetings. Each meetings consists of planning, observation, implementation, and reflection. The subject of this study is the fifth grade students. The data comes from the fifth grade students, fifth grade teacher, observer, and documents. The validity of the data source uses a technique of triangulation and the sources of data triangulation. Learning has increased from cycle I to cycle II. Evidenced from mastery learning students reached 86.90% in the 1st cycle and 100% in the 2nd cycle. The conclusion of this study is the application of TAI type with multimedia can improve natural science learning about hydrology cycle fifth grade students elementary school. Keywords: Team Asissted Individualization (TAI), Multimedia, Natural Science  Abstrak: Penerapan Tipe Team Assisted Individualization (TAI) dengan Multimedia dalam Peningkatan Pembelajaran IPA tentang Daur Air Kelas V SD. Tujuan penelitian ini adalah untuk mendeskripsikan dan meningkatkan pembelajaran IPA tentang daur air siswa kelas V di SD, serta menemukan kendala dan solusi dalam penerapan tipe TAI dengan multimedia. Penelitian ini merupakan  penelitian tindakan kelas kolaboratif yang dilaksanakan dalam 2 siklus dengan 5 pertemuan. Setiap pertemuan terdiri dari tahap perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian ini adalah siswa kelas V. Data berasal dari siswa kelas V, guru kelas V, observer dan dokumen. Validitas data menggunakan triangulasi data dan sumber data. Pembelajaran mengalami peningkatan dari siklus  I hingga siklus II. Dibuktikan dari ketuntasan belajar siswa mencapai 86,90% pada siklus I dan 100% pada siklus II. Simpulan penelitian ini adalah penerapan tipe TAI  dengan multimedia dapat meningkatkan pembelajaran IPA tentang daur air siswa kelas V SD.Kata Kunci: Team Asissted Individualization (TAI), Multimedia, IPA